2007
DOI: 10.1111/j.1600-065x.2006.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

γδ T‐cell receptors: functional correlations

Abstract: The gammadelta T-cell receptors (TCRs) are limited in their diversity, suggesting that their natural ligands may be few in number. Ligands for gammadeltaTCRs that have thus far been determined are predominantly of host rather than foreign origin. Correlations have been noted between the Vgamma and/or Vdelta genes a gammadelta T cell expresses and its functional role. The reason for these correlations is not yet known, but several different mechanisms are conceivable. One possibility is that interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 94 publications
(103 reference statements)
2
108
0
1
Order By: Relevance
“…Expansion of the  T-cell subset has been also documented in the context of various infections including Mycobacterium and cytomegalovirus [20]. However [21]. At birth, the repertoire of  T cells in cord blood is broad with no apparent restriction [22].…”
Section: Discussionmentioning
confidence: 99%
“…Expansion of the  T-cell subset has been also documented in the context of various infections including Mycobacterium and cytomegalovirus [20]. However [21]. At birth, the repertoire of  T cells in cord blood is broad with no apparent restriction [22].…”
Section: Discussionmentioning
confidence: 99%
“…2F). Interestingly, V␥1.1 ϩ V␦6.3 ϩ ␥␦ T cells are the predominant subset of ␥␦ NKT cells, and readily produce effector cytokines (17,21,22).…”
Section: Itk ؊/؊ Mice Contain Increased Proportions Of ␥␦ T Cells Submentioning
confidence: 99%
“…Basal levels of IFN␥ mRNA were similar between the WT and Itk Ϫ/Ϫ ␥␦ T cells; after stimulation, both cell types produced IFN␥, although WT ␥␦ T cells showed higher levels of IFN␥ mRNA compared with ␥␦ T cells lacking Itk. Based on the high proportion of V␥1.1 ϩ V␦6.3 ϩ ␥␦ T cells present in Itk Ϫ/Ϫ mice and the previous association of this ␥␦ T cell subset with dual production of IL-4 and IFN␥ (21,22), we also examined WT and Itk Ϫ/Ϫ ␥␦ T cells for expression of the transcription factor PLZF. PLZF has recently been found to be critical for the development and effector function of TCR␣␤ ϩ NKT cells, where it promotes the simultaneous production of IL-4 and IFN␥ (18,19).…”
Section: Itk ؊/؊ Mice Contain Increased Proportions Of ␥␦ T Cells Submentioning
confidence: 99%
“…2 cd T cells expressing different Vcs have different effects on the immune responses. 8 Recent studies revealed a correlation between TCR-Vc expression and functional differentiation, 9,10 thus emphasizing the biological significance of the cd TCR segregation in the mouse. Nevertheless, specific evidence concerned with IL-17 producing cd T cells suggests that, at least in this case, the correlation between cd TCR expression and function is merely coincidental-waves of cd T cells expressing certain TCRs coincide with a thymic environment that temporarily favors TH17 differentiation.…”
Section: The CD T-cell Receptorsmentioning
confidence: 99%